Patents, human rights, and access to medicines / Emmanuel Kolawole Oke, University of Edinburgh. - Oke, Emmanuel Kolawole (Cambridge University Press, 2022)
Patent rights on pharmaceutical products are one of the factors responsible for the lack of access to affordable medicines in developing countries. In this work, Emmanuel Kolawole Oke provides a systematic analysis of the tension between patent rights and human rights law, contending that, in order to preserve their patent policy space and secure access to affordable medicines for their citizens, developing countries should incorporate a model of human rights into the design, implementation, interpretation, and enforcement of their national patent laws. Through a comprehensive analysis of court decisions from three key developing countries (India, Kenya, and South Africa), Oke assesses the effectiveness of national courts in resolving conflicts between patent rights and the right to health, and demonstrates how a model of human rights can be incorporated into the adjudication of patent rights.